DESCRIPTION OF A NEW LATE MIOCENE AMERICAN BADGER (TAXIDIINAE) UTILIZING HIGH-RESOLUTION X-RAY COMPUTED TOMOGRAPHY - Owen P.R. (My University, 2006)
Chamitataxus avitus gen. et sp. nov. is a primitive American badger recovered from late Miocene fossil-bearing sediments of the Chamita Formation in northern New Mexico, USA. The holotype and only known specimen is an almost complete skull with left and right I1-M1. Description of Chamitataxus avitus is facilitated by high-resolution X-ray computed tomography (HRXCT), which provides non-destructive visualization of the internal morphology. Features such as the hollowing of the mastoid region and the septate and greatly inflated tympanic bulla of Chamitataxus avitus are made visible and provide evidence supporting Taxidiinae. The invasion of the nasal bone by a small sinus, the nasoconchal sinus, is documented for the first time in both Taxidea taxus and Chamitataxus avitus. The HRXCT data complement information obtained from external and more traditional examination of the skull. The P4 does not exhibit the development of a medial shelf and hypocone observed in Pliotaxidea and Taxidea. This is evidence for the acquisition of a P4 medial shelf and hypocone by taxidiine badgers independent from that of meline (Eurasian) badgers. The morphological information obtained from this study provides new insight into the evolution and ecomorphology of taxidiine badgers. © 2006 The Palaeontological Association.
Keywords: BADGER; COMPUTED TOMOGRAPHY; ECOMORPHOLOGY; MIOCENE; MUSTELID; TAXIDIINAE; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен